Perbandingan Tanggung Jawab Hukum Pekerja Outsourcing di Indonesia dan Amerika Serikat dalam Hukum Ketenagakerjaan - Aisya Wiradrana Wasistha; Agus Prihartono; Dede Agus (Indonesian Journal Publisher, 2025)
This study aims to compare the legal responsibility regulations governing outsourcing workers in Indonesia and the United States from the perspective of Indonesia’s Law No. 13 of 2003 on Manpower and the National Labor Relations Act (NLRA). The research was conducted to identify the differences in worker protection, especially regarding employment contracts, wages, social security, and legal certainty. Using a normative juridical method with statutory, conceptual, and comparative approaches, data were obtained from primary legal materials such as legislation, secondary materials including academic literature and journals, and tertiary materials as supporting references. The analysis employed a descriptive-analytical method to compare the substance and implementation of outsourcing regulations in both countries. The results indicate that Indonesia’s outsourcing regulations remain limited and often create legal uncertainty, particularly after the enactment of the Job Creation Law, which expanded outsourcing practices without strengthening worker protection. Conversely, the United States provides more comprehensive protection through the NLRA, the Fair Labor Standards Act (FLSA), and the Civil Rights Act, ensuring the right to organize, regulating minimum wages and working hours, and prohibiting discrimination. The study concludes that weak supervision, unclear legal interpretation, and low compliance are the main obstacles in Indonesia, while in the U.S., the “at-will” employment system remains the key factor reducing job security for outsourcing workers.